Introduction to Word 2007 - Conway, Pamela; Safari eBooks ([S.l.] : CompuWorks, 2012)
"This course covers the basic functions and features of Word 2010. After an introduction to Word's window components, you will learn how to enter and edit text, save and navigate documents and use Help. You will also learn how to enhance the appearance of a document by using various formatting options. The course will cover creating tables, inserting basic headers and footers, proofing documents, and printing and emailing documents."--Resource description page.
Title from title screen.
Publication information from resource description page (viewed Apr. 8, 2013).
Presenter, Pamela Conway.
Keywords: Microsoft Word; Word processing; Electronic books